(untitled) - Foster, S. Thomas (Upper Saddle River, 2004)
This book is used by our university as a textbook for the subject of ¡§Service Quality Management". I found that this book can give us much useful information of service quality. Since service quality is very important in service industry nowadays; there is a need to understand more about how to manage service quality in order to deliver good-quality service and gain customer loyalty.
Keywords: Quality of products,Quality control